Analisis Rasio Keuangan Daerah untuk Mengukur Kinerja Keuangan Pemerintah Kabupaten/Kota di Jawa Barat - Zulkarnain Zulkarnain (Cakrawala Repositori IMWI, 2020)
Measurement of the financial performance of local governments can show the financial condition of local governments and the ability of the region to explore and manage the existing sources of funds. A good regional financial performance can be seen from its effectiveness in exploring regional potentials, lower dependency on the central government, and a larger portion of PAD to finance regional development. This study seeks to measure the financial performance of the District-City Government in West Java by using a regional financial ratio measurement tool, which consists of the Fiscal Decentralization Ratio, the Regional Government Financial Dependency Ratio, the PAD Effectiveness Ratio, and the Capital Expenditure Ratio. The results of the measurement of the Fiscal Decentralization Ratio concluded that the financial capacity of the Regency-City Government in West Java is still classified as "LESS". The measurement results of the Regional Government Financial Dependency Ratio concluded that there were no local governments whose financial dependence on transfer funds falls into the "LOW" category. The results of the measurement of the PAD Effectiveness Ratio concluded that the majority of local governments in West Java had been effective and very effective in realizing the PAD target. And the results of the Capital Expenditure Ratio measurement concluded that there had been efforts from the District-City Government in West Java to maximize Capital Expenditures. This study has several limitations. Subsequent research can add the scope of testing or assessment to be more comprehensive, for example by conducting tests or studies on the determinants of the financial performance of local governments or the impact resulting from the factual conditions of the financial performance of local governments.